A Noradrenergic Lesion Attenuates Surgery-Induced Cognitive Impairment in Rats by Suppressing Neuroinflammation - Wang, Jiayu; Zhou, Ying; Li, Ke; Li, Xiaofeng; Guo, Meimei; Peng, Mian (Frontiers in Molecular Neuroscience, 2021)
Postoperative cognitive dysfunction (POCD) is a common postoperative neurocognitive complication in elderly patients. However, the specific pathogenesis is unknown, and it has been demonstrated that neuroinflammation plays a key role in POCD. Recently, increasing evidence has proven that the locus coeruleus noradrenergic (LCNE) system participates in regulating neuroinflammation in some neurodegenerative disorders. We hypothesize that LCNE plays an important role in the neuroinflammation of POCD. In this study, 400 μg of N-(2-chloroethyl)-N-ethyl-2-bromobenzylamine (DSP-4) was injected intracerebroventricularly into each rat 7 days before anesthesia/surgery to deplete the locus coeruleus (LC) noradrenaline (NE). We applied a simple laparotomy and brief upper mesenteric artery clamping surgery as the rat POCD model. The open field test, novel objection and novel location (NL) recognition, and Morris water maze (MWM) were performed to assess postoperative cognition. High-performance liquid chromatography (HPLC) was used to measure the level of NE in plasma and brain tissues, and immunofluorescence staining was applied to evaluate the activation of microglia and astrocytes. We also used enzyme-linked immune-sorbent assay (ELISA) to assess the levels of inflammatory cytokines and brain-derived neurotrophic factor (BDNF). Pretreatment with DSP-4 decreased the levels of systemic and central NE, increased the level of interleukin-6 (IL-6) in the plasma at 6 h after the surgery, decreased the concentration of IL-6 in the prefrontal cortex and hippocampus, and decreased the level of interleukin-1β (IL-1β) in the plasma, prefrontal cortex, and hippocampus at 1 week postoperatively. In addition, DSP-4 treatment attenuated hippocampal-dependent learning and memory impairment in rats with POCD, with a downregulation of the activation of microglia and astrocytes in the prefrontal cortex and hippocampus. In conclusion, these findings provide evidence of the effects of LCNE in modulating neuroinflammation in rats with POCD and provide a new perspective in the prevention and treatment of POCD.